Volumetric studies of alcohols in water and aqueous micelle solutions of cetyltrimethylammonium bromide - Parvin, T; Alauddin, M; Rokonuzzaman, M (Journal of the Bangladesh Chemical Society, 2012)
The volumetric properties of 1-propanol, cyclohexanol and butoxyethanol in water and CTAB water mixtures have been studied. The apparent molar volumes of 1-propanol, cyclohexanol and butoxyethanol in water and in aqueous solutions of CTAB were determined from density data. The partial molar volumes of the alcohols in water and aqueous micelle solutions at infinite dilution, V20(mic) were obtained from apparent molar volume data and compared with the corresponding values. The standard partial molar expansibilities, E20(mic) of the solubilizates were evaluated from V20(mic) data at various temperatures. The volumetric studies of alcohols in CTAB micelles indicate that alcohols on the average are preferentially solubilized in the palisade layer of the micelle and increasing amount of each is transferred more deep into the palisade layer of the micelle with increasing surfactant concentration and temperature. The results of standard partial molar volume, V20 and standard partial molar expansibilities, E20 are reported and discussed. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9703 Journal of Bangladesh Chemical Society, Vol. 24(2), 143-157, 2011